2007
DOI: 10.1038/sj.mp.4002093
|View full text |Cite
|
Sign up to set email alerts
|

Lithium regulates adult hippocampal progenitor development through canonical Wnt pathway activation

Abstract: Neural stem cells give rise to new hippocampal neurons throughout adulthood, and defects in neurogenesis may predispose an individual to mood disorders, such as major depression. Our understanding of the signals controlling this process is limited, so we explored potential pathways regulating adult hippocampal progenitor (AHP) proliferation and neuronal differentiation. We demonstrate that the mood stabilizer lithium directly expands pools of AHPs in vitro, and induces them to become neurons at therapeutically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
161
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 48 publications
17
161
2
1
Order By: Relevance
“…Possible mechanisms favoring neuronal differentiation may involve the BDNF pathway (Su et al, 2009), ERK-and CREBdependent pathways (Kim et al, 2004), as well as the Wnt pathway (Wexler et al, 2008). However, in this study, the proportion of neuronal and astrocyte differentiation was not different between the lithium and vehicle groups.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Possible mechanisms favoring neuronal differentiation may involve the BDNF pathway (Su et al, 2009), ERK-and CREBdependent pathways (Kim et al, 2004), as well as the Wnt pathway (Wexler et al, 2008). However, in this study, the proportion of neuronal and astrocyte differentiation was not different between the lithium and vehicle groups.…”
Section: Discussioncontrasting
confidence: 66%
“…The number of BLBP-positive cells was not increased by lithium treatment in control animals, indicating that lithium stimulated proliferation of progenitor cells rather than the asymmetric division of stem cells. Wexler reported that lithium enhances cell proliferation by activating the canonical Wnt pathway (Wexler et al, 2008). GSK-3b is a critical mediator of the Wnt/bcatenin signaling pathway and lithium inhibits the activation of GSK-3b directly and indirectly (Chalecka-Franaszek and Chuang, 1999;Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…inhibitor lithium chloride (LiCl), which stabilizes and activates β-catenin, induces adult hippocampal progenitor cell proliferation [132]. LiCl treatment also stimulates cell proliferation and neuronal fate specification in a mouse model of Alzheimer's disease [133].…”
Section: Wnt Signaling and Adult Neurogenesis: Intracellular Componentsmentioning
confidence: 99%
“…We also showed that agomelatine increases the phosphorylation of ERK1/2, AKT, and GSK3b known to transduce the effects of antidepressant agent and mood stabilizers on proliferation of hippocampal neural progenitors (Jiang et al, 2005;Wexler et al, 2008;Silva et al, 2008). The enhanced survival of new granule cells may also be related to the activation of MAPK (ERK1/2) and PI-3K signaling pathways, as previously shown in vitro (Almeida et al, 2005), and hippocampal NSCs can be protected from apoptosis by antidepressant-induced activation of BDNF and the MAPK pathway (Peng et al, 2008).…”
Section: Adult Neurogenesis and Antidepressantmentioning
confidence: 99%